Volleyball players training to overcome the competitive obstacles and difficulties - Kamalieva, G. A. (The Russian Journal of Physical Education and Sport, 2016)
Overcoming the mental stress is an integral part of volleyball players training to overcome obstacles and competitive challenges through the development of theoretical and methodological and technological support of training athletes to overcome competitive challenges and obstacles. This targeted training includes theoretical, practical and control classes. Thus, the model training volleyball players to overcome obstacles and competitive challenges is implemented.